2024
DOI: 10.1186/s12944-024-02012-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and suicidal ideation in adults: a population-based study in the United States

Guangwei Qing,
Wenpeng Deng,
Yuxin Zhou
et al.

Abstract: Background The ratio of non-high-density lipoprotein cholesterol (non-HDL-C) to high-density lipoprotein cholesterol (HDL-C) (NHHR) serves as a reliable lipid indicator associated with atherogenic characteristics. Studies have indicated a potential connection between suicidality and lipid metabolism. This research aims to investigate any possible association between the NHHR and the emergence of suicidal ideation within the confines of the study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This study revealed that compared with the individual measurements of non-HDL-c and HDL-c, the NHHR has superior diagnostic predictive value for the risk of developing HUA. Additionally, further RCS analysis indicated a nonlinear, inverse U-shaped association between the NHHR and the risk of developing HUA, consistent with previous studies on the connection between the NHHR and suicidal ideation [ 31 ]. This study extends the use of lipid ratios and fills the gaps in previous research, suggesting that the NHHR might be a promising marker for predicting HUA.…”
Section: Discussionsupporting
confidence: 89%
“…This study revealed that compared with the individual measurements of non-HDL-c and HDL-c, the NHHR has superior diagnostic predictive value for the risk of developing HUA. Additionally, further RCS analysis indicated a nonlinear, inverse U-shaped association between the NHHR and the risk of developing HUA, consistent with previous studies on the connection between the NHHR and suicidal ideation [ 31 ]. This study extends the use of lipid ratios and fills the gaps in previous research, suggesting that the NHHR might be a promising marker for predicting HUA.…”
Section: Discussionsupporting
confidence: 89%
“…MDD patients with higher TC levels were more likely to undergo FSA in the past 14 days. In recent years, there have been an increasing number of studies on biomarkers associated with suicidal behavior, and lipid levels have emerged as a potential factor in this regard (52)(53)(54)(55). Metabolic syndrome is common in patients with MDD, and it is associated with suicide attempts (56).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NHHR was utilized as the exposure variable. As described in previous literature [ 14 , 21 ], NHHR represents the ratio of non-HDL-C to HDL-C. Non- HDL-C is determined by subtracting HDL-C from the total cholesterol (TC) level.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing from prior studies [ 14 , 21 ], we incorporated variables potentially impacting the link between NHHR and T2DM. Included covariates encompass age, sex, race, PIR, marital status, BMI, waist circumference, education level, smoking, alcohol consumption, creatinine, moderate recreational activities, blood urea nitrogen, serum uric acid, dietary cholesterol on the first day, stroke, and hypertension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation